Improve islamic financial literacy and optimize the islamic economy through financial technology: INPES apps - Hidayat, Yusuf Murtadlo; Machmud, Amir (Universitas Pendidikan Indonesia, 2019)
In recent years, sharia financial technology has been growing rapidly in Indonesia. In early 2019, there were 55 sharia fintech companies registered as members of the Indonesian Fintech Sharia Association (AFSI). However, interestingly, according to survey conducted by The Financial Services Authority (OJK), the Islamic financial literacy index is still very low (8.11%), whereas understanding / knowing the law of muamalah is obligatory for every Muslim before they make any transaction. INPES platform integrates sharia learning and sharia financing in an online based application, where users must complete their muamalah course before they access financing services. This application can be applied at amil zakat institutions, Islamic boarding schools, and other non-bank financial institutions.In recent years, sharia financial technology has been growing rapidly in Indonesia. In early 2019, there were 55 sharia fintech companies registered as members of the Indonesian Fintech Sharia Association (AFSI). However, interestingly, according to survey conducted by The Financial Services Authority (OJK), the Islamic financial literacy index is still very low (8.11%), whereas understanding / knowing the law of muamalah is obligatory for every Muslim before they make any transaction. INPES platform integrates sharia learning and sharia financing in an online based application, where users must complete their muamalah course before they access financing services. This application can be applied at amil zakat institutions, Islamic boarding schools, and other non-bank financial institutions.